Development of Performance, Physiological and Technical Capacities During a Six-Month Cross-Country Skiing Talent Transfer Program in Endurance Athletes - Rune Kjøsen Talsnes; Rune Kjøsen Talsnes; Tor-Arne Hetland; Xudan Cai; Xudan Cai; Øyvind Sandbakk (Frontiers Media S.A., 2020)
Purpose: To examine the development of performance, physiological and technical capacities as well as the effect of sport background among runners, kayakers and rowers when transferred to cross-country (XC) skiing over a 6-month training period.Methods: Twenty-four endurance athletes (15 runners and 9 rowers/kayakers; 15 men and 9 women) were tested for performance, physiological and technical capacities during treadmill running and roller-ski skating, double-poling ergometry, as well as upper-body, one-repetition maximum-strength (1 RM) at baseline (pre) after three (mid) and 6-months (post) of XC ski-specific training.Results: Peak treadmill speed when roller-ski skating improved significantly (13%, P < 0.01) from pre-post, with a larger improvement in runners than in kayakers/rowers (16 vs. 9%, P < 0.05), whereas peak speed in running was unchanged. Average power output during 5-min and 30-s ergometer double-poling tests improved by 8% and 5% (both P < 0.01), with improvement found only in runners on the 30-s test (8 vs. −2% in kayakers/rowers, P < 0.01). Peak oxygen uptake (VO2peak) in running and double-poling ergometry did not improve, whereas VO2peak in roller-ski skating improved by 5% in runners (P < 0.05). Submaximal gross efficiency increased by 0.6%-point and cycle length by 13%, whereas 1 RM in seated pull-down and triceps press increased by 12 and 11%, respectively (all P < 0.05).Conclusion: Six-months of XC ski-specific training induced large improvements in sport-specific performance which were associated with better skiing efficiency, longer cycle length, and greater 1RM upper-body strength in a group of endurance athletes transferring to XC skiing. Furthermore, larger sport-specific development was found in runners compared to kayakers/rowers.